2012
DOI: 10.1007/s00198-012-2018-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of osteoporotic fracture risk factors and antiosteoporotic treatments in the Valencia region, Spain. The baseline characteristics of the ESOSVAL cohort

Abstract: The prevalence of certain fracture risk factors not included in the FRAX tool (sedentary life, falls, low calcium intake) is high. In young women, their low risks estimated by FRAX contrast with the high figures for densitometry testing and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 37 publications
1
25
2
4
Order By: Relevance
“…In applying the Spanish FRAX ® model to the FRO-DOS cohort the baseline risks of fracture expected at 10 years were 1.22 and 5.28% for FF and POF respectively. These results are lower than those reported in the ECOSAP study which were 3.67 and 8.78% respectively 5 , slightly higher than those of the FRIDEX cohort, 0.95 and 3.8% 7 , and similar to those of the Valencia group (1.9 and 5.5%) 10 ,…”
Section: Discussioncontrasting
confidence: 76%
“…In applying the Spanish FRAX ® model to the FRO-DOS cohort the baseline risks of fracture expected at 10 years were 1.22 and 5.28% for FF and POF respectively. These results are lower than those reported in the ECOSAP study which were 3.67 and 8.78% respectively 5 , slightly higher than those of the FRIDEX cohort, 0.95 and 3.8% 7 , and similar to those of the Valencia group (1.9 and 5.5%) 10 ,…”
Section: Discussioncontrasting
confidence: 76%
“…In the GLOW study, the highest prevalence was seen in Southern Europe (28%), with a somewhat lower prevalence in North America (23%) and Northern Europe (23%) (31). However, a recent study carried out in Valencia (Spain) of 5310 women aged !50 yr reported that 15.8% had a history of fracture (30). A smaller proportion of underweight subjects and differences in other factors such as ethnic composition, nutritional habits, and lifestyle may contribute to these geographical differences.…”
Section: Discussionmentioning
confidence: 92%
“…Despite the significant influence of BMD on the overall risk of fracture, several studies have shown that taken in isolation, it fails to deliver a cost-effective population screening test [7][8][9] . The current practice in most developed countries is to identify patients at high risk of fragility fractures taking into account the presence of other risk factors besides densitometric osteoporosis [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%